Methylenetetrahydrofolate reductase gene polymorphisms and executive functions in a sample of Egyptian children with attention-deficit hyperactivity disorder. Issue 4 (October 2018) - Elwasify, Mohamed; Elwasify, Mahmoud; Mostafa, Maged; Saleh, Elsayed; Hamdey, Ibrahim; Barakat, Doaa
Abstract : Objective: The aim was to investigate two gene polymorphisms, at base pair 677 and 1298, and their relation to executive functions in Egyptian children with attention-deficit hyperactivity disorder (ADHD). Participants and methods: A case–control study was conducted on 65 children with ADHD and 69 healthy controls to assess the role of methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms using PCRs and restriction fragment length polymorphisms. Vanderbilt Parent Rating Scale, Kiddie Schedule for Affective Disorders and Schizophrenia, Wechsler Intelligence Scale, and Wisconsin Card Sorting Test were used for diagnosis and evaluation. Results: Statistically significant differences were found in genotype distributions of the MTHFR polymorphism (C677T alleles and A1298C alleles) and in the number of categories completed of Wisconsin test between the two groups. The comparison of clinical variables of ADHD group between each of MTHF C677T gene polymorphisms as well as MTHF A1298C gene polymorphisms showed no statistically significant difference. Conclusion: This study provides evidence that MTHFR C677T and A1298C polymorphisms may have relationship with ADHD subtypes and with the impairment of executive function of children with ADHD.